Effect of in situ synthesis of Si2N2O on microstructure and the mechanical properties of fused quartz ceramics. Issue 7 (May 2020) - Wang, Yingxia; Hou, Qinglin; Tian, Liang; Chen, Pingfei; Xiao, Jiakai
Abstract: Si/SiO2 composite billets were prepared using a low-toxicity gel system, and the resulting billets were sintered at high temperature in nitrogen to synthesize Si2 N2 O in the central position of the fused silica ceramic matrix. The influences of in situ synthesized Si2 N2 O on the microstructure and mechanical properties of fused silica ceramics were studied. The results show that Si/SiO2 composite billets can be used to synthesize spike-like and fibrous Si2 N2 O in situ in nitrogen at 1450 °C. Si2 N2 O synthesized in situ can improve the mechanical properties and microstructure of quartz ceramics. When the Si/SiO2 composite billet is sintered in nitrogen at 1450 °C for 2 h, the volume density and bending strength of the quartz ceramics can reach 2.36 g/cm 3 and 114.37 MPa, respectively.